Their Own Worst Enemies: Behavioural Finance and the Investments of Australian Households - Bebbington, Christopher Anthony (Curtin University, 2024)
This dissertation has used data from two Australian superannuation funds to explore how behavioural biases influence decision making within retirement savings schemes. Overall, the findings reveal that members within retirement savings schemes succumb to behavioural biases, and, that these biases may detrimentally impact their ability to adequately finance their retirement lifestyles.